Navigating Classical Texts in A Digital Age: A Phenomenological Study of Gen Z and Gen Alpha’s Experiences in Arabic Literacy - Zulfan Syahansyah; Abdurrahman Abdurrahman (PT. Riset Press International, 2026)
This study addresses the widening cognitive gap in Arabic literacy among digital-native generations within traditional Indonesian pesantren settings. The research aims to explore the essential lived experiences of Gen Z and Gen Alpha students in interpreting classical Arabic texts amidst digital culture. Utilizing an interpretative phenomenological approach, data were gathered through in-depth interviews and participant observations at Pesantren Al-Munawwariyah. The findings reveal a “Cross-Spatial Cognitive Negotiation” and a “Digital Cognitive Filter”, where students navigate between traditional spiritual identity and modern algorithmic logic. While Gen Z demonstrates functional adaptation, Gen Alpha exhibits linguistic alienation requiring visual-interactive mediation. This study identifies a “Techno-Traditional Paradox”, highlighting that the literacy crisis stems from methodological irrelevance rather than a decline in sacred values. Consequently, this study contributes a novel cross-generational socio-cognitive framework to Arabic educational psychology, while providing a strategic roadmap for educators to implement “Generatively Responsive Pedagogy”, ensuring classical Arabic remains an existential, living language in the era of information disruption.